Terence Davies - Koresky, Michael, 1979- (University of Illinois Press, 2014)
Called the most important British filmmaker of his generation, Terence Davies made his reputation with modern classics like 'Distant Voices', 'Still Lives', and 'The Long Day Closes'. His idiosyncratic and unorthodox narrative films defy easy categorization; though they would seem to exist within the realms of realism and personal memory cinema, the films lay bare the director's personal pain in a daringly abstract way. Film critic Michael Koresky explores the unique emotional tenor of Davies' work by focusing on four paradoxes within the director's oeuvre: films that are autobiographical yet fictional; melancholy yet elating; conservative in tone and theme yet radically constructed; and obsessed with the passing of time yet frozen in time and space.
Keywords: Davies, Terence, -- 1945-2023 -- Criticism and interpretation.; Davies, Terence, -- 1945-2023 -- Interviews.; Davies, Terence, -- 1945-; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- Direction & Production.; Electronic books.; Criticism, interpretation, etc.; Interviews